MFI Network: A Web-Based Platform For Handyman Job Opportunities - Mokdin, Ahmadur Rohma Norol Riskoh; Bin Sahid, Mohd Zanes (Applied Information Technology And Computer Science, 2026)
Furniture shopping has evolved significantly with the rise in e-commerce, MFI Hardware, a prominent hardware shop in Kampung Melayu Sungai Buloh, Selangor, serves as a key resource for handymen, customers, and subcontractors. However, reliance on traditional methods like handwritten notes and business cards has led to operational efficiencies, including cluttered records and difficulty in accessing information. This project introduces a digital platform to address these challenges by enabling handymen to register and promote services, customers to search for and book handymen seamlessly, and subcontractors to generate accurate budgets with access to hardware prices. With a user-friendly design and usability testing, the platform aims to create a cleaner, more organized workspace, enhance customer satisfaction, and boost the visibility of local handymen. MFI Hardware will strengthen its reputation as a modern, community-focused business, and fostering local economic growth.